Performance Control of Road and Bridge Preservation Projects Using Earned Value Management (EVM) Method - Javan Agustian Setyagraha; Budi Witjaksana; Hanie Teki Tjendani (Asian Journal of Social and Humanities, 2024)
The Situbondo – Ketapang – Banyuwangi Road and Bridge Preservation Project experienced changes in the work area, requiring additional design. Asphalt overlay work was halted awaiting the test results of Asphalt Modiv PG – 70 from the Pusjatan Road Material Laboratory in Bandung, resulting in a delay in week 40 by -0.813%. Specifically, AC - WC and AC - BC asphalt work was delayed, significantly impacting the overall project performance. Cost and time analysis are crucial to address this issue. The Earned Value Management (EVM) method is used to evaluate project duration and costs. The Cost Performance Index (CPI) indicates good cost performance (>1), but the Schedule Performance Index (SPI) indicates schedule delays (0.983 < 1). The final project cost is estimated at Rp 112,439,121,070.91, with a completion time of 453 days, three days longer than planned. Effective strategies are needed in time control and design adjustments to complete the project according to expected standards.